Human Resource Ethics in Malaysia: A Study of Malaysian Employees’ Perception of Business Ethics and Its Relatedness to the Local Culture - Kuan, Kenneth Hwai Kien (2005)
This research presents an exploratory view of the Malaysian working professional’s attitude towards business ethics. The study was done in view of the dearth of empirical study on this topic in Malaysia. The subject of business ethics is gaining popularity, due mainly to two factors. The first is the higher level of education attained by Malaysians as a result of development. Secondly, the effect of globalisation in which the Western world, primarily led by the United States has imposed their Corporate Social Responsibility (CSR) values into the eastern culture. These two factors have made it interesting to explore what the current view of the Malaysian working professional is towards business ethics. The study is based on the opinions of 81 working professionals who were randomly selected across several industries in the Klang Valley region. Three main questions were investigated in this study. The first question was to find out the Cynicism Quotient of respondents. Therefore this hypothesis was a confidence-interval building exercise to see where a Malaysian would reside on a scale of 1 to 60. A high score reflected a higher level of cynicism. The second hypothesis was to see if Malaysians viewed themselves as being more ethical than their peers at work. The third hypothesis investigated the effect of gender on Malaysians’ ethical perceptions. The results indicate that the average Malaysian professional is somewhat cynical about business ethics. It also reveals that Malaysians perceive themselves to be more ethical than their counterparts at work. Finally, while there was no significant difference found in the overall ethical perception of males versus females, there was evidence that in specific ethical situations, women have a tendency to be more relationship driven than men in the work environment. I have analysed the results of the study in relation to the rich cultural heritage of Malaysia. Much of the discussion section explains the findings within this context.